USM ARTS STUDENT GOES MINIMALIST, TO HIGHLIGHT THE BEAUTY OF ART - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 24 May 2016 As life becomes more intense, the minimalist style is slowly gaining influence among the Millennials for them to invest their time in the important things in life.